Prognostic Determinants Analysis and Nomogram for Bone Malignant Vascular Tumors: A Surveillance, Epidemiology and End Results (SEER) Analysis - Hu, Sunli (Med Sci Monit, 2020)
BACKGROUND: The aim and objective of our investigations were to explore the prognostic value of various clinical and pathological factors of bone malignant vascular tumors and establish a nomogram for their outcome predictions. MATERIAL/METHODS: All data of primary bone malignant vascular tumors (MVTs) patients were randomly selected from the Surveillance, Epidemiology and End Results (SEER) database. However, selected patients were clinically diagnosed with various cancers during 1988–2015. The potential prognostic factors were analyzed using SPSS (Windows, version 22.0). All prognostic factors were combined to formulate a nomogram to predict the overall survival (OS). RESULTS: A total of 266 selected patients were included in our study. In the univariate model, age (P<0.001), sex (p=0.0255), primary site (P<0.001), surgery (P<0.001), histologic type (P<0.001), metastasis (p=0.000), and pathological grade (P<0.001) were statistically significant for patient survival. The results of Cox analysis revealed that age (≥64) HR: 3.636, 95% CI [1.955–6.762], p=0.000, the primary site in skull HR: 2.6, 95% CI [1.584–4.268], p<0.001], without surgery HR: 1.473 95% CI [1.239–1.751], p<0.001, metastasis HR: 3.076 95% CI [1.983–4.771] p=0.000, man HR 1.802, 95% CI [1.032–3.004], p=0.045, and high malignant grade HR: 3.029, 95% CI [2.101–4.366], p=0.003 were independent unfavorable prognostic factors. Angiosarcoma had highest mortality rate among all vascular malignancies. The nomogram predicting overall survival achieved a C-index of 0.694 (95% CI 0.631, 0.745) in the SEER cohort. CONCLUSIONS: Surgery can significantly increase OS survival time for bone MVTs, and low-grade malignancy is a significant factor for OS. However, advanced age, tumor metastasis, primary site in skull, AS, and male sex are predictors of poor prognosis.